Portable paper-in-tip spray ionization for the direct mass spectrometric analysis of target analytes in biofluid samples. Issue 3 (23rd December 2021) - Lu, Fangfang; Zheng, Yajun; Zhang, Yuan; Ma, Qiang; Zhang, Zhiping
Abstract : Portable sampling of target analytes in complex biofluid samples makes mass spectrometric analysis more efficient. Abstract : Portable sampling of target analytes in complex biofluid samples makes mass spectrometric analysis more efficient. This study reports the development of paper-in-tip spray ionization for solid-phase microextraction and in situ electrospray of therapeutic drugs and proteins in complex biological matrices using a piece of hydrophobic paper substrate. This technique possesses a long (more than 8 min) and stable spray duration with only 20 μL of spray solvent. The entire analytical process for a complex sample can be completed in less than 1.5 min and enables high sensitivity (picogram-per-milliliter level) and high quantitation precision.